MARCO THE DAMNED AS THE SPECIFIC MANIFESTATION OF AUTHOR’S AESTHETIC CONSCIOUSNESS IN THE PLAYS BY VASYL PACHOVSKYI - Verlata, A. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights the problem of Marko the Damned character’s realization as the main symbolic image in the plays by Vasyl Pachovskyi. The primary focus of the article is on the correlation of the playwright’s creative thinking and this image. It is emphasized on the conceptual significance of this character in the works by the author.